2016
DOI: 10.5812/ijp.7727
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal Dieulafoy Lesion Detected by Intraoperative Endoscopy in a Child

Abstract: Introduction: Dieulafoy lesion is an unusual cause of gastrointestinal bleeding in which significant, and often recurrent, hemorrhage occurs from a pinpoint non-ulcerated arterial lesion. It is usually located in gastric fundus, and is extremely rare in children. Case Presentation: In this study, we present a male adolescent with jejunal Dieulafoy lesion. The patient was admitted to the hospital due to hematochezia and hypotension. No active bleeders were identified on endoscopy, colonoscopy, and double-balloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…During surgery, intraoperative enteroscopy can be performed to help localize the bleeder. 70 The findings of this review showed that the single-and double-balloon enteroscopies were the ideal techniques, with the diagnostic yields of 96% and 98%, respectively. These device-assisted enteroscopies are more efficacious in identifying Dieulafoy's lesion as they complement noninvasive techniques like capsule endoscopy.…”
Section: Comorbid Conditionsmentioning
confidence: 90%
“…During surgery, intraoperative enteroscopy can be performed to help localize the bleeder. 70 The findings of this review showed that the single-and double-balloon enteroscopies were the ideal techniques, with the diagnostic yields of 96% and 98%, respectively. These device-assisted enteroscopies are more efficacious in identifying Dieulafoy's lesion as they complement noninvasive techniques like capsule endoscopy.…”
Section: Comorbid Conditionsmentioning
confidence: 90%
“…All of the patients had no recurrence after the surgery. 11,12,13,14,15,16 This report shows that all of the articles have no recurrence after surgery, even though the surgery is done laparoscopically.…”
Section: Discussionmentioning
confidence: 68%
“…Six articles combined open surgery with intraoperative enteroscopy, and others with laparoscopic surgery in combination with enteroscopy, super-selective angiography, and embolization, and laparotomy RA alone with preoperative angiography. 11,12,13,14,15,16…”
Section: Figure1mentioning
confidence: 99%
“…In most of these cases, DLs were detected by multiple modalities, some of which were repeated in various attempts in some cases, and tailored combinations of measures were performed to control the bleeding. [12][13][14][15][16][17][18][19][20][21][22][23] In conclusion, jejunal DLs presenting with untypical manifestations should not be ignored when they cause episodes of sudden, recurrent, and massive GI bleeding. Bleeding events may be triggered after gastroenteritis.…”
Section: Discussionmentioning
confidence: 99%